Longitudinal predictors for internalizing and externalizing symptomatology at age 4: KUNO-Kids cohort study - Jarvers, Irina; Kandsperger, Stephanie; Ecker, Angelika; Brandstetter, Susanne; Kabesch, Michael; Köninger, Angela; Melter, Michael; Kerzel, Sebastian; Kittel, Jochen; Apfelbacher, Christian; Brunner, Romuald (Frontiers in Psychiatry, 2024)
IntroductionNumerous early-life risk factors are thought to significantly contribute to the development of psychological problems in toddlerhood. However, these factors have seldom been investigated concomitantly and longitudinally, and few studies include both mothers and fathers. This study examines the longitudinal impact of early environmental, parental, and child-specific risk factors on children’s internalizing and externalizing symptomatology at age 4.MethodsFamilies were recruited from a perinatal center at birth and completed self-report questionnaires at birth, 4 weeks postpartum, 6 months postpartum, and annually thereafter. The final population-based sample consisted of n = 560 mothers (and fathers) who gave birth after June 2015, with children who turned 4 years old before March 31, 2021. The primary outcomes, children’s internalizing and externalizing symptomatology at age 4, were measured using the Strengthsand Difficulties Questionnaire. Linear mixed effect models were used to estimate growth curves for predictors between 4 weeks and 4 years postpartum, which were subsequently entered into multivariable linear regressions to predict internalizing and externalizing symptomatology at age 4.ResultsThe study identified several key risk factors: environmental (lack of social support, lower parental education, male sex), parental (poor parental mental health, increased parenting stress, parental sleep difficulties) and child-specific (children’s low physical health, children’s reduced sleep quality, temperament).DiscussionThe findings underscore that most identified risk factors are related to children’s temperament, mental and physical health of parents, their experienced stress, and families’ social support networks. These insights highlight the importance of targeted interventions focusing on improving parental mental health, reducing stress, and enhancing social support to mitigate early-life psychological problems in children.